The Role of Bloom’s Taxonomy in Improving Listening Skill - kizi, Makhmudova Munira Xaitboy; kizi, Mustafoyeva Nilufar Ulash (European Journal of Life Safety and Stability (2660-9630), 2023)
This article deals with the importance of Bloom’s Taxonomy in improving listening skill in English language. Although Bloom’s Taxonomy is considered one of the best methods which is used in an English classroom, there are hardly any information or materials about the usage in the increase of listening skill. In this work the role of this method in the involvement of teaching and learning will be analyzed.